2009
DOI: 10.7748/ns2009.04.23.31.44.c6933
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ attitudes towards the sexuality of colorectal patients

Abstract: This article reviews the literature on nurses' attitudes towards sexuality and highlights a range of studies carried out on functional outcomes following colorectal surgery. The article provides nurses with an insight into colorectal cancer, the prevalence of sexual dysfunction in men and women following colorectal surgery and the importance of addressing the various aspects of sexuality in a sensitive manner to provide patients with holistic care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
0
7
0
2
Order By: Relevance
“…Most studies reported that the main reason that nurses' do not discuss sexual concern and problems with their patients is because of insufficient time, focusing on the cancer treatment and patients' unwillingness to talk about the related issues, insufficient knowledge, general views and attitudes towards sexual issues and the concern that the patient would feel a loss of intimacy (Tsaii, 2004;Beck and Justham, 2009;Saunamaki et al, 2010;Huang et al, 2013). In a systematic review by Kotronoulas and et al (2009), which covers 18 studies, it is stressed that taboos and prejudices of nurses would hinder discussions on sexual issues (Kotronoulas et al, 2009).…”
Section: Umran Oskay Et Almentioning
confidence: 99%
“…Most studies reported that the main reason that nurses' do not discuss sexual concern and problems with their patients is because of insufficient time, focusing on the cancer treatment and patients' unwillingness to talk about the related issues, insufficient knowledge, general views and attitudes towards sexual issues and the concern that the patient would feel a loss of intimacy (Tsaii, 2004;Beck and Justham, 2009;Saunamaki et al, 2010;Huang et al, 2013). In a systematic review by Kotronoulas and et al (2009), which covers 18 studies, it is stressed that taboos and prejudices of nurses would hinder discussions on sexual issues (Kotronoulas et al, 2009).…”
Section: Umran Oskay Et Almentioning
confidence: 99%
“…), head and neck (Low et al . ), and colorectal cancer (Beck ). Despite this, health professionals have been reported to be less likely to discuss sexual changes with individuals or couples experiencing a non‐sexual cancer (Ussher et al .…”
Section: Introductionmentioning
confidence: 99%
“…Such research has focused almost exclusively on either men or women, and on cancers that directly affect reproductive or sexual sites of the body (for an exception see Hordern & Street 2007a), including breast (Ussher et al 2013a), gynaecological (Stead et al 2003), prostate and testicular cancers (Danile & Haddow 2011;Jankowska 2012). However, there is increasing evidence that both men and women across a range of cancer types report changes to their sexuality post cancer (Perz et al 2014), including lung ), lymphatic (Jonker-Pool et al 2004Jarden et al 2012), colon (van der Horst-Schrivers et al 2009), non-Hodgkin lymphoma (Beckjord et al 2011), head and neck (Low et al 2009), and colorectal cancer (Beck 2009). Despite this, health professionals have been reported to be less likely to discuss sexual changes with individuals or couples experiencing a non-sexual cancer (Ussher et al 2013c).…”
Section: Introductionmentioning
confidence: 99%
“…Certain studies show that nursing personnel report that they do not consider patients' sexual problems to be an area of nursing care, which is contradictory as the task is to provide care based on a holistic perspective (Stead et al . ; Darst ; Beck & Justham ).…”
Section: Introductionmentioning
confidence: 99%